Որդան կարմիր - Ստեփանյան, Աշոտ («Զանգակ - 97»)
The wicker art is one of the finest sphere of the Armenian applied art and with its decorative structure, distinctive peculiarities of ornament, use of thread and paint materials has created such originality of the Armenian weave, which brought to it world fame and became a finest part of the Armenian applied art history and the historical-cultural achievement of a whole people.
Keywords: Մշակույթ